Feasibility and acceptability of a motivational intervention combined with text messaging for alcohol and sex risk reduction with emergency department patients: a pilot trial. (4th March 2019) - Mastroleo, Nadine R.; Celio, Mark A.; Barnett, Nancy P.; Colby, Suzanne M.; Kahler, Christopher W.; Operario, Don; Suffoletto, Brian P.; Monti, Peter M.
Abstract: Background: Interventions aimed at reducing co-occurring heavy drinking and risky sexual behavior among Emergency Department (ED) patients require feasibility and acceptability to optimally engage individuals. Objectives: This pilot study explored the feasibility and acceptability of an interactive text-messaging (TM) supplement to a brief in-person intervention previously found successful in reducing alcohol use and condomless sex. Methods: Using a mixed-method design, ED patients with past hazardous alcohol use and condomless sex ( N = 20) were randomly assigned to receive either a Motivational Intervention + TM or Brief Advice + TM. All participants completed exit interviews at four weeks follow-up, and transcripts were transcribed and coded to identify themes. We evaluated feasibility through quantitative assessment of TM response rates and latency to response, while acceptability was evaluated through thematic analysis of exit interviews. Results: Findings provide support for the delivery of an integrated and personalized MI and TM. Participants engaged positively with the TM intervention and qualitative interviews offered strong support for the acceptability while offering information necessary to enhance the TM component. Conclusions: Integrating MI with TM is feasible and acceptable to at-risk ED patients and could facilitate behavior changes beyond MI alone.